The effectiveness of a sustained nurse home visiting intervention for Aboriginal infants compared with non-Aboriginal infants and with Aboriginal infants receiving usual child health care: a quasi-experimental trial - the Bulundidi Gudaga study - Lynn Kemp; Rebekah Grace; Elizabeth Comino; Lisa Jackson Pulver; Catherine McMahon; Elizabeth Harris; Mark Harris; Ajesh George; Holly A. Mack (BMC, 2018)
Abstract Background In Australia there is commitment to developing interventions that will 'Close the Gap' between the health and welfare of Indigenous and non-Indigenous Australians and recognition that early childhood interventions offer the greatest potential for long term change. Nurse led sustained home visiting programs are considered an effective way to deliver a health and parenting service, however there is little international or Australian evidence that demonstrates the effectiveness of these programs for Aboriginal infants. This protocol describes the Bulundidi Gudaga Study, a quasi-experimental design, comparing three cohorts of families from the Macarthur region in south western Sydney to explore the effectiveness of the Maternal Early Childhood Sustained Home-visiting (MECSH) program for Aboriginal families. Methods Mothers were recruited when booking into the local hospital for perinatal care and families are followed up until child is age 4 years. Participants are from three distinct cohorts: Aboriginal MECSH intervention cohort (Group A), Non-Aboriginal MECSH intervention cohort (Group B) and Aboriginal non-intervention cohort (Group C). Eligible mothers were those identified as at risk during the Safe Start assessment conducted by antenatal clinic midwives. Mothers in Group A were eligible if they were pregnant with an Aboriginal infant. Mothers in Group B were eligible if they were pregnant with a non-Aboriginal infant. Mothers in Group C are part of the Gudaga descriptive cohort study and were recruited between October 2005 and May 2007. The difference in duration of breastfeeding, child body mass index, and child development outcomes at 18 months and 4 years of age will be measured as primary outcomes. We will also evaluate the intervention effect on secondary measures including: child dental health; the way the program is received; patterns of child health and illness; patterns of maternal health, health knowledge and behaviours; family and environmental conditions; and service usage for mothers and families. Discussion Involving local Aboriginal research and intervention staff and investing in established relationships between the research team and the local Aboriginal community is enabling this study to generate evidence regarding the effectiveness of interventions that are feasible to implement and sustainable in the context of Aboriginal communities and local service systems. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12616001721493 Registered 14 Dec 2016. Retrospectively registered.